Proteomic Analysis of S-Nitrosation Sites During Somatic Embryogenesis in Brazilian Pine, Araucaria angustifolia (Bertol.) Kuntze - Borges Araujo, Alexandre Junio; Cerruti, Giovanni Victorio; Zuccarelli, Rafael; Rodriguez Ruiz, Marta; Freschi, Luciano; Singh, Ratna; Moerschbacher, Bruno Maria; Floh, Eny Iochevet Segal; Wendt dos Santos, André Luis (Frontiers in Plant Science, 2022)
Cysteine S-nitrosation is a redox-based post-translational modification that mediates nitric oxide (NO) regulation of various aspects of plant growth, development and stress responses. Despite its importance, studies exploring protein signaling pathways that are regulated by S-nitrosation during somatic embryogenesis have not been performed. In the present study, endogenous cysteine S-nitrosation site and S-nitrosated proteins were identified by iodo-TMT labeling during somatic embryogenesis in Brazilian pine, an endangered native conifer of South America. In addition, endogenous –S-nitrosothiol (SNO) levels and S-nitrosogluthatione reductase (GSNOR) activity were determined in cell lines with contrasting embryogenic potential. Overall, we identified an array of proteins associated with a large variety of biological processes and molecular functions with some of them already described as important for somatic embryogenesis (Class IV chitinase, pyruvate dehydrogenase E1 and dehydroascorbate reductase). In total, our S-nitrosoproteome analyses identified 18 endogenously S-nitrosated proteins and 50 in vitro S-nitrosated proteins (after GSNO treatment) during cell culture proliferation and embryo development. Furthermore, SNO levels and GSNOR activity were increased during embryo formation. These findings expand our understanding of the Brazilian pine proteome and shed novel insights into the potential use of pharmacological manipulation of NO levels by using NO inhibitors and donors during somatic embryogenesis.